Implementasi Augmented Reality Sebagai Media Pengenalan Monumen Bersejarah Gorontalo Berbasis Android - Kolopita, Roji Anugrah; Y Lamasigi, Zulfriyanto; Pakaya, Roys (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2023)
Abstract - Augmented Reality is a technology that combines 2-dimensional objects or 3- dimensional objects into images on markers and then projects the 3D objects directly. It is very useful as a tourism data media to attract tourists both domestic and foreign, as well as to share different experiences and guidance in mastering each place or tourism attraction visited. In making this application the researcher uses unity3D by applying the Marker-Based Tracking method. This marker method is used to detect markers in an Augmented Reality application so that it can display 3D visualizations of Gorontalo historical monuments. The utilization of Augmented Reality technology in this recognition system can provide an overview of the Gorontalo Historical Monument so that it can increase the attractiveness of the public to get to know historical monuments in Gorontalo. Keywords: augmented reality, android, marker-based tracking, Vuforia